101k views
3 votes
Find the difference.

Find the difference.-example-1

1 Answer

4 votes


5.\\12(3)/(10)-7(7)/(10)=11(10+3)/(10)-7(7)/(10)=11(13)/(10)-7(7)/(10)=4(6)/(10)=4(6:2)/(10:2)=\boxed{5(3)/(5)}\\\\11-7=4\\\\(13)/(10)-(7)/(10)=(13-7)/(10)=(6)/(10)\\\\6.\\8(1)/(6)-3(5)/(6)=7(6+1)/(6)-3(5)/(6)=7(7)/(6)-3(5)/(6)=(7-3)+(7-5)/(6)=4(2)/(6)=4(2:2)/(6:2)=\boxed{4(1)/(3)}


9.\\7(1)/(6)-2(5)/(6)=6(6+1)/(6)-2(5)/(6)=6(7)/(6)-2(5)/(6)=(6-2)+(7-5)/(6)=4(2)/(6)=\boxed{4(1)/(3)}\\\\10.\\9(3)/(12)-4(7)/(12)=8(12+3)/(12)-4(7)/(12)=8(15)/(12)-4(7)/(12)=(8-4)+(15-7)/(12)=4(8)/(12)\\\\=4(8:4)/(12:4)=\boxed{4(2)/(3)}

User Greg Weber
by
5.3k points